Suppression of Murine Lupus by CD4+ and CD8+ Treg Cells Induced by T Cell–Targeted Nanoparticles Loaded With Interleukin‐2 and Transforming Growth Factor β. Issue 4 (5th March 2019) - Horwitz, David A.; Bickerton, Sean; Koss, Michael; Fahmy, Tarek M.; La Cava, Antonio
Abstract : Objective: To develop a nanoparticle (NP) platform that can expand both CD4+ and CD8+ Treg cells in vivo for the suppression of autoimmune responses in systemic lupus erythematosus (SLE). Methods: Poly(lactic‐co‐glycolic acid) (PLGA) NPs encapsulating interleukin‐2 (IL‐2) and transforming growth factor β (TGFβ) were coated with anti‐CD2/CD4 antibodies and administered to mice with lupus‐like disease induced by the transfer of DBA/2 T cells into (C57BL/6 × DBA/2)F1 (BDF1) mice. The peripheral frequency of Treg cells was monitored ex vivo by flow cytometry. Disease progression was assessed by measuring serum anti–double‐stranded DNA antibody levels by enzyme‐linked immunosorbent assay. Kidney disease was defined as the presence of proteinuria or renal histopathologic features. Results: Anti‐CD2/CD4 antibody–coated, but not noncoated, NPs encapsulating IL‐2 and TGFβ induced CD4+ and CD8+ FoxP3+ Treg cells in vitro. The optimal dosing regimen of NPs for expansion of CD4+ and CD8+ Treg cells was determined in in vivo studies in mice without lupus and then tested in BDF1 mice with lupus. The administration of anti‐CD2/CD4 antibody–coated NPs encapsulating IL‐2 and TGFβ resulted in the expansion of CD4+ and CD8+ Treg cells, a marked suppression of anti‐DNA antibody production, and reduced renal disease. Conclusion: This study shows for the first time that T cell–targeted PLGA NPs encapsulating IL‐2 and TGFβ can expand both CD4+ and CD8+ Treg cells in vivo and suppress murine lupus. This approach, which enables the expansion of Treg cells in vivo and inhibits pathogenic immune responses in SLE, could represent a potential new therapeutic modality in autoimmune conditions characterized by impaired Treg cell function associated with IL‐2 deficiency.